2022
DOI: 10.1097/lgt.0000000000000672
|View full text |Cite
|
Sign up to set email alerts
|

Precise Measurement of the Thickness of Vaginal Intraepithelial Neoplasia

Abstract: ObjectivesAlthough carbon dioxide laser vaporization is frequently used for treating vaginal intraepithelial neoplasia (VaIN), the optimal depth of epithelial destruction with laser vaporization requires elucidation. We aimed to evaluate VaIN depth and better illustrate epithelial destruction during laser vaporization.Materials and MethodsWe included 246 women diagnosed with VaIN (low-grade VaIN [VaIN 1], 123 women; high-grade VaIN [VaIN 2/3], 123 women) using colposcopy-directed biopsy at our hospital from Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Exploring the depth of the involved and non-involved vaginal epithelium in 246 patients with VaIN, Cui et al found that the thickness of the lesion was generally <1 mm for patients of all ages, except in rare cases of visible lesions with papillary hyperplasia. The mean thickness of the epithelium involved was 0.4 mm and it did not differ between the grades of VaIN 80 …”
Section: Methodsmentioning
confidence: 74%
“…Exploring the depth of the involved and non-involved vaginal epithelium in 246 patients with VaIN, Cui et al found that the thickness of the lesion was generally <1 mm for patients of all ages, except in rare cases of visible lesions with papillary hyperplasia. The mean thickness of the epithelium involved was 0.4 mm and it did not differ between the grades of VaIN 80 …”
Section: Methodsmentioning
confidence: 74%
“…The mean thickness of the epithelium involved was 0.4 mm and it did not differ between the grades of VaIN. 80 CO 2 laser vaporization can be performed under local anesthesia. Epithelial destruction to a depth of 1-1.5 mm, including the zone of thermal necrosis, seems to be sufficient to destroy the epithelium containing SIL, without damage to the underlying structures.…”
Section: Ablative Methodsmentioning
confidence: 99%
“…The mean thickness of the epithelium involved was 0.4 mm and it did not differ between the grades of VaIN. 80 …”
Section: Methodsmentioning
confidence: 99%
“…Средняя толщина пораженного эпителия составляла 0,4 мм и не различалась в зависимости от степени VaIN по результатам Cui C. с соавт. [62]. CO 2 -лазерная вапоризация может проводиться под местной анестезией.…”
Section: абляционные методыunclassified